S140 Gdf-15 Down-regulation Of Muscle Microrna Drives Increased Sensitivity To Tgf-β Signalling; A Novel Mechanism In Intensive Care Unit Acquired Weakness. (10th November 2014) - Bloch, SAA; Lee, JY; Syburrah, T; Rosendahl, U; Kemp, PR; Griffiths, MJD; Polkey, MI
Abstract : Introduction: Intensive care unit acquired weakness (ICUAW) is common and associated with significant morbidity. We previously identified GDF-15, a TGF-β super-family member, as a potential driver of acute muscle wasting in a novel human model of ICUAW (Crit Care Med 2013;2013;41:982). In the current study we investigated the potential mechanisms by which GDF-15 may contribute to the development of ICUAW. Dysregulation of muscle microRNAs has been described in muscle disorders. MicroRNAs are essential for muscle homeostasis and their expression can be influenced by inflammatory cytokines. Furthermore muscle microRNAs may down-regulate TGF-β signalling. However, the function of microRNAs in ICUAW has not previously been described. We hypothesised that down-regulation of muscle microRNAs, driven by GDF-15, would lead to increased sensitivity to TGF-β signalling in muscle of patients with ICUAW. Methods: We conducted an observational study of 20 patients with ICUAW and 7 elective surgical controls. Subjects underwent rectus femoris muscle biopsy and blood sampling. Muscle specimens were examined for mRNA and microRNA expression of target genes by qPCR. Plasma samples were tested for GDF-15 concentration (ELISA). Histology samples were stained for pSMAD2/3 nuclear positivity. To examine the effects of GDF-15 on target genes, differentiated C2C12 myotubes were treated with GDF-15 for 4 days. The effect of over-expression of miR-181a in C2C12 myoblasts on TGF-β signalling was also examined. Results: Compared with controls, patients with ICUAW had greater GDF-15 mRNA expression in muscle (median 2-fold higher; p = 0.006) and concentration in plasma (median 7239 vs. 2454 pg/ml; p = 0.001). MicroRNAs involved in muscle homeostasis were significantly lower in muscle from patients with ICUAW. Both log[GDF-15 mRNA] and log[plasma GDF-15] were significantly negatively correlated with log[microRNA expression]. GDF-15 treatment of myotubes significantly elevated expression of muscle atrophy-related genes and down-regulated expression of muscle microRNAs. miR-181a suppressed TGF-β responses in myoblasts, suggesting increased sensitivity to TGF-β in ICUAW muscle. Consistent with this, nuclear phospho-SMAD2/3 and CYR61 mRNA expression were increased in ICUAW muscle. Discussion: By suppressing expression of muscle microRNAs GDF-15 may increase sensitivity to TGF-β signalling, thus promoting muscle wasting in ICUAW. This study identifies both GDF-15 and associated microRNA as potential therapeutic targets in ICUAW.